Analisis Kebijakan Efisiensi Anggaran terhadap Kualitan Penyusunan RKA di PT. XYZ - Fatima Thuzahra; Tantina Haryati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Budget efficiency is a key strategy in addressing resource constraints and the increasing demand for organizational performance. This study aims to analyze the adaptation of government budget efficiency principles in the preparation of the Work and Budget Plan (RKA) at PT. XYZ, a private real estate company undergoing a transformation into a regionally owned enterprise (BUMD). The research employed a descriptive qualitative approach using in-depth interviews and document analysis. The findings indicate that budget efficiency was implemented through evaluations of previous budget realizations, the establishment of measurable priorities, and active involvement of work units. This efficiency had a positive impact on the quality and accountability of the RKA, although challenges remain, particularly in coordination and the absence of a standardized operating procedure. These findings contribute theoretically to the literature on budgeting in the non-government sector and offer practical implications for companies undergoing institutional transformation toward becoming BUMDs.